2018
DOI: 10.1016/j.jobcr.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of turmeric in management of alveolar osteitis (dry socket): A randomised clinical study

Abstract: In this study there was significant reduction in pain, inflammation & discomfort after turmeric and ZOE dressing. Wound healing was seen faster, than dressing with ZOE. There is no side effect of Turmeric. Statistical analysis was done p < 0.05, was found statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Due to the increasing popularity of Aloe vera L. in medicine and dentistry, its effectiveness in the healing of post extraction sockets was tested. A cross-sectional randomized interventional study conducted on 40 patients demonstrated that the extract from this plant improved postoperative wound healing and decreased the severity of symptoms, compared to only analgesic treatment [Lone et al 2018].…”
Section: Post Extraction Socket Healingmentioning
confidence: 99%
“…Due to the increasing popularity of Aloe vera L. in medicine and dentistry, its effectiveness in the healing of post extraction sockets was tested. A cross-sectional randomized interventional study conducted on 40 patients demonstrated that the extract from this plant improved postoperative wound healing and decreased the severity of symptoms, compared to only analgesic treatment [Lone et al 2018].…”
Section: Post Extraction Socket Healingmentioning
confidence: 99%
“…The use of turmeric at the site of an injury by topical application promotes healing of wounds. Therefore the turmeric can be used in different forms for treating different ailments including surgical wounds (Parveen et al, 2017).…”
Section: Biological Importance Of Curcuminmentioning
confidence: 99%
“…Being an old surgical puzzle, many different methods have been advocated to treat alveolar osteitis, such as the application of local turmeric [17], zinc oxide eugenol, alvogyl, honey or vitamin C [18], and socket irrigation with hydrogen peroxide [19]. However, these conventional treatment approaches merely solve the symptoms but do not target the key etiology.…”
Section: Introductionmentioning
confidence: 99%